Dye-sensitized lanthanide-doped upconversion nanoparticles for water detection in organic solvents - Yu, Zhongzheng (2022)
The use of fluorescent probes to detect water content in organic solvents is highly desirable in chemical industries. Optimal fluorescent probes are expected to achieve rapid tests with a high sensitivity. Most existing fluorescent probes use water as a quencher to turn off the fluorescence and are not able to detect water in very low concentrations. We report a nanoformulation containing lanthanide-doped upconversion nanoparticles (UCNPs) coated with a very high concentration of ICG to detect water content in organic solvents via a turn-on process with an ultrahigh sensitivity at the ppm level. It is based on our unexpected observation that UCNPs coupled to a high concentration of ICG dye and dispersed in an organic solvent exhibit enhancement of emission upon addition of water. A turn-off detection process can also be achieved when the water content is higher (>0.2% v/v, 2000 ppm). We propose the underlying sensitization mechanism as involving the interaction of polar water with ICG, influencing the quenching between dye molecules and energy transfer from dye molecules to UCNPs. We hope our approach could provide a guide for the design of fluorescent nanosensors for water detection in organic solvents and also deepen the understanding of the energy transfer processes from organic dye to UCNPs.